2013
DOI: 10.1371/journal.pone.0064973
|View full text |Cite
|
Sign up to set email alerts
|

The miR-184 Binding-Site rs8126 T>C Polymorphism in TNFAIP2 Is Associated with Risk of Gastric Cancer

Abstract: Background TNFAIP2 is a crucial gene involved in apoptosis. Single nucleotide polymorphisms (SNPs) in its miRNA binding sites could modulate functions of the miRNA-target genes and thus risk of cancers. In this study, we investigated associations between potentially functional SNPs in the miRNA binding sites of the 3′UTR of TNFAIP2 and gastric cancer risk in a US population.MethodsWe conducted a case-control study of 301 gastric cancer patients and 313 cancer-free controls frequency-matched by age, sex and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 29 publications
6
30
1
Order By: Relevance
“…Overexpression of TNFAIP1 or TNFAIP2 correlates with tumor invasion and metastasis, and serves as an independent prognostic indicator for breast cancer (9) and nasopharyngeal carcinoma (15). The TNFAIP2 miRNA binding site (s8126 T>C SNP) is also correlated with a significantly elevated risk of gastric cancer, suggesting a marker for susceptibility to gastric cancer (16). To verify the correlation of TNFAIP1 expression with OS, we examined the expression of TNFAIP1 in human OS tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TNFAIP1 or TNFAIP2 correlates with tumor invasion and metastasis, and serves as an independent prognostic indicator for breast cancer (9) and nasopharyngeal carcinoma (15). The TNFAIP2 miRNA binding site (s8126 T>C SNP) is also correlated with a significantly elevated risk of gastric cancer, suggesting a marker for susceptibility to gastric cancer (16). To verify the correlation of TNFAIP1 expression with OS, we examined the expression of TNFAIP1 in human OS tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These genes include TNFAIP2 [19], FGFR4 [20][21][22], CXCL10 [23], CEP55 [24], CXCL1 [25,26], LIMK1 [27], LAMC2 [28], APOE [29], INHBA [30], OSMR [31,32], APOC1 [33], KLF4 [34], MMP14 [35], ADH1C [36], COL6A3 [37,38], CCT2 [39], NOL8 [40], EPHB4 [41] and MCM2 [42,43]. Ye et al reported that high expression of FGFR4 protein is associated with a poor prognosis in patients with advanced GC and expedites the progress of advanced GC [20].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs in miRNA binding sites could affect its binding affinity to target genes. A recent study showed that the TNFAIP2 miRNA binding site rs8126 T>C SNP may be a marker for susceptibility to GC [19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, downregulating MiR-29c conferred a growth advantage on tumor cells via aberrant expression of RCC2 in gastric carcinoma cells [24]. Of note, the SNP (single nucleotide polymorphism) of TNFAIP2 (the key gene in apoptosis) in miRNA binding site, rs8126 T>C, caused high susceptibility to gastric cancer [25], which also indicate the role of miRNA as tumor suppressor. Together, miRNA can serve as oncogenes or tumor suppressors during tumorigenesis of gastric cancer and may be a potential gastric cancer therapeutic target.…”
Section: The Involvement Of Mirnas As Oncogenes or Tumor Suppressors mentioning
confidence: 99%